Surface Hardening Technology with a Concentrated Energy Source - Ryazantsev, Anton; Nechaev, Vasyl; Bondar, Olena (International Journal of Integrated Engineering, 2019)
The article is devoted to the increase of wear resistance of large-modular gears due to the application of the innovative method of plasma surface hardening working surfaces of teeth. The method of determination and estimation of the residual resource of large-modular gear transmissions after plasma surface hardening is developed and the influence of technological parameters of this process on wear resistance and mechanisms of deterioration of the surface layer have been investigated. The process of plasma surface hardening has been experimentally investigated, an estimation of the obtained physical and mechanical properties and hardness of the processed material during plasma heating has been made. The increase of durability of the work of large-modular gears passing by the plasma surface hardening has been experimentally investigated and the calculations on durability have been performed for the wear parameter, and it has been established that the application of this heat treatment method increases the durability 2.28 times. A complex of specialized equipment was developed for the implementation of the technological scheme of plasma surface hardening of the large-modular gears' working surfaces without melting, using the original design of the magnetic-deflection system for the creation of an external magnetic field.